2000
DOI: 10.1346/ccmn.2000.0480208
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Alkyltrimethylammonium-Intercalated Magadiite

Abstract: Abstraet--Cetyltrimethylammonium-and tetradecyltrimethylammonium-intercalated magadiites were prepared by direct syntheses, starting from sodium metasilieate (NaaO/SiO2 = 1.0) and nitric acid. Total substitution of sodium by cetyltrimethylammonium or tetradecyltrimetbylammoniurn cations was not achieved in the range of surfactant : silicon molar ratios used in this study. When a phosphoniun-based surfactant replaces the ammonium surfactants in the same procedure, the result of the synthesis is a mixture of qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
2
21
0
2
Order By: Relevance
“…The Na-magadiite (Mag) was synthesized under highly alkaline conditions and sodium ions were present as expected in the claylike solid structure [23]. Under the basic conditions of silica gel under hydrothermal conditions at 150 • C, hydroxide ions have reacted with acid sites of silica producing water and leaving behind negative sites, which are counterbalanced by the sodium ions originally associated with the hydroxide ions.…”
Section: Magadiite Characterizationmentioning
confidence: 99%
“…The Na-magadiite (Mag) was synthesized under highly alkaline conditions and sodium ions were present as expected in the claylike solid structure [23]. Under the basic conditions of silica gel under hydrothermal conditions at 150 • C, hydroxide ions have reacted with acid sites of silica producing water and leaving behind negative sites, which are counterbalanced by the sodium ions originally associated with the hydroxide ions.…”
Section: Magadiite Characterizationmentioning
confidence: 99%
“…The aggregates of the nano-sheets might be ascribed to Magadiite phase (Fig. 1d) 28 . The ZSM-5 exhibited conventional coffin-like morphology, with the crystal size of up to ~5 μm.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to the slight decrease of the relative crystallinity (Table 1). It should be pointed out that when the active seeds were replaced by TPAOH (TPAOH/SiO2 ratio = 0.00175, which was equal to that when 0.5% of active seeds were used), impurity of obvious Magadiite phase could be observed for sample Z-TPA-120, leading to the further decreasing of the relative crystallinity 28 . This proved the effectiveness of the active seeds in directing to the synthesis of zeolite ZSM-5.…”
Section: Resultsmentioning
confidence: 99%
“…66 The new process was reported to be more economic. Structural diversity of MAG has been documented by Scholzen et al 67 The layered silicic acids (MAG, kenyaite, octosilicate/ ilerite and kanemite) have been also prepared hydrothermally with good control of platelets dimensions, 68 by means of templated preparations that led to organomodified materials, 69 using a one-pot method with structure directing agents, 70 or by using solid-state reactions. 71 Beneke et al also reported syntheses of layered lithium sodium silicate (silinaite).…”
Section: Synthetic Clays-methods Of Preparationmentioning
confidence: 99%